Exploring the Influence of Quezon City Scholarships on Advancing Educational Equity and Fostering Social Mobility - Gracilla, Rowena L.; Arreglo, Rona-Jean R.; Bago, Nackelyn D.; Romero, Kristine Joy E.; Ulam, Jeffrey A.; Malang, Bernandino P.; Malang, Jocelyn DS. (Future Science / FSH-PH Publications, 2024)
The study,